Controle semi-ativo de suspensão automotiva utilizando o modelo “1/2-car” para veículos “off-road” - Koshino, Felipe Haga (Universidade Federal de São Carlos, 2022)
Automotive suspensions are systems that seek to reduce vertical acceleration in vehicles and reduce vibrations caused by imperfections in the pavement, resulting in increased stability and passenger comfort, using a passive system formed by dampers and springs. The present work aimed to develop a semi-active control system for automotive suspensions subject to unstable terrain, seeking to improve passenger comfort, as well as vehicle rolling stability compared to the common passive system. The control in question is, in a simplified way, formed by an actuator between the suspended and unsprung masses of the car, electronically. In the proposed work, we chose to use a system with variation of the fluid flow contained in the damper through a valve whose opening varies according to the input received. Initially, the model of ½ vehicle systems, also called half-car, was considered and then the passive and semi-active conditions were simulated in Matlab® using a PID controller. There was a substantial reduction in the settling time of the system by approximately 40%. In addition, there was a reduction of about 3% in the amplitude of the vertical displacement and reductions of approximately 4% and 12% in the rotation amplitude of the system, respectively. Thus, it can be said that the general and specific objectives were met, enabling an improvement in the response of the suspension system as a whole, that is, the proposed semi-active system presented satisfactory results in the following items: settling time and overshoot, when compared to the common passive system.
Semi-active control of a vehicle suspension using a half-car off-road mechanical model
Keywords: Suspensão semiativa; Semi-active control; Controle PID; PID control; Coeficiente de amortecimento variável; Variable damping coefficient; CAN-AM UTV; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS